Nekrosis daun rambutan, penyebab dan pengaruhnya terhadap hasil=Leaf necrosis in rambutan, its causal factors and effect on yield. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Leaf necrosis symptom often flourishes in rambutan trees during dry season. No scientific-based information was determined concerning the causes and its effect on crop yield A relatively strong dry wind that prevailed during a long period of dry season, and soil potassium status, were suspected as the main cause for the occurrence of leaf necrosis. Two experiments were conducted to ditermine the cause of leaf necrosis in rambutan trees, using rambutan seedlings and farmers-own rambutan trees. In the first experiment, pot grown rambutan seedlings of cv. Rapiah of five months old, were placed in the greenhouse of the Department of Agronomy Experimental Station GMU. Wind blowers were used to generate a 44.2 rninlin wind flow at 29.1Â°C and a 37.4 &min wind flow at 39.5Â°C. Potassium chloride fertilizer was applied to both sets of pots at the rates of 0, 10, 20, 30, and 40 g per pot. The combination treatments were repeated 5 times. In the second experiment, several healthy and necrotic plants of rambutan cvs. 'Lebakbulus', 'Binjai', and 'Rapiah' were used for observations. The experiment was conducted on eight years old rambutan trees at farmer's garden at Salaman, Regency of Magelang, Central Java during the period of August 1996 to February 1997. Observations included fruit yield, leaf potassium content, relative water content in leaves, soil potassium content, and soil moisture content under the canopy of rambutan trees. It was observed that symptoms of rambutan leaf necrosis were started to develop when the leaf potassium content and the relative water content of the leaves were less than I % and 80 % respectively. The lower they were, the wider the symptoms appeared. Symptoms of necrosis were also found in rambutan trees grown in rich potassium soils, provided the soil moisture content is low as commonly occur during the thy season. Leaf necrosis in rambutan trees resulted in lower fruit yield of cvs. 'Lebakbulus' and Tinjai'. This reduction in fruit yield was in the range of 80 to 100 %, especially among trees which had a high fruit yield at the last season. Yield reduction was due to the reduced number offruits per tree, as well as the fruit size.